PATTERN OF CORONARY ARTERIAL DISTRIBUTION AND ITS RELATION TO CORONARY ARTERY DIAMETER - Kaimkhani, Zahid Ali; Ali, M. Moazzam; Faruqi, Azhar M. A. (Journal of Ayub Medical College Abbottabad, 2005)
Background: This study was carried out to determine the pattern of coronary arterial distribution and its relation with coronary artery diameter in adult Pakistani population as demonstrated by selective coronary angiography. Methods: Consecutive series of 220 adult subjects who underwent diagnostic coronary angiography at National Institute of Cardiovascular Disease (NICVD) between May 2000 and December 2000 were studied. Patients whose age was more than 18 years, with no apparent disease in the proximal arterial segment, proximal artery and tip of the catheter in the middle of the frame and catheter of a No. 6 French size of same manufacturer used were included in this study. Patients who were given vasodilator before or during the procedure, angiograms showing complete proximal occlusions or ectatic arteries were excluded. Results: Sixty percent subjects had right dominance pattern of which 78.1% were male and 21.8% female. By contrast 15% had left coronary dominance, of which 78.7 % were male and 21.2% female. Where as, 24% patients had co-dominant (balanced) circulation with 83.3 % male and 16.6 % female. In patients with left dominant pattern, the mean diameter of the right coronary artery (RCA) was significantly smaller (p<0.001) as compared to dominant right or co-dominant pattern. Where as in patients with right dominant pattern, the mean diameter of the circumflex (CX) artery was significantly smaller (p<0.001) as compared to dominant left. Conclusion: The coronary arterial distribution in Pakistani population is not significantly different from that given in the literature and the diameter of the RCA and the CX artery are significantly affected by dominance pattern. Key words. Coronary anatomy, dominant pattern, diameter, angiography, Pakistani population.